2017
DOI: 10.1530/eje-16-0808
|View full text |Cite
|
Sign up to set email alerts
|

Bone material strength index as measured by impact microindentation is altered in patients with acromegaly

Abstract: Our data indicates that tissue-level properties of cortical bone are significantly altered in patients with controlled acromegaly after reversal of long-term exposure to pathologically high GH and IGF-1 levels. Our findings also suggest that methods other than DXA should be considered to evaluate bone fragility in patients with acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 27 publications
4
49
0
Order By: Relevance
“…Similar to prior reports we found a weak negative association between BMSi and age, (15) and a weak positive association between BMSi and aBMD by DXA. (18) Our results are also consistent with studies that have shown BMSi to be lower in select patient populations with known skeletal fragility, including those with a history of bone stress injury, (25) type 2 diabetes, (9)(10)(11) HIV, (12) acromegaly, (13) and Gaucher's disease. (14) Our study is the first to examine BMSi in patients with DRFs and is the first to suggest a relationship between occurrence of DRF and BMSi that is independent of femoral neck aBMD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to prior reports we found a weak negative association between BMSi and age, (15) and a weak positive association between BMSi and aBMD by DXA. (18) Our results are also consistent with studies that have shown BMSi to be lower in select patient populations with known skeletal fragility, including those with a history of bone stress injury, (25) type 2 diabetes, (9)(10)(11) HIV, (12) acromegaly, (13) and Gaucher's disease. (14) Our study is the first to examine BMSi in patients with DRFs and is the first to suggest a relationship between occurrence of DRF and BMSi that is independent of femoral neck aBMD.…”
Section: Discussionsupporting
confidence: 87%
“…(5) Although cyclic microindentation is mainly used for characterization of excised bone samples and in animal studies, impact microindentation is designed specifically for clinical use. (6)(7)(8) Although the precise mechanical properties reflected by impact microindentation remain to be established, recent studies using the technique have shown cortical bone properties measured in vivo at the tibial diaphysis to be worse in select patient populations with known skeletal fragility, including those with type 2 diabetes, (9)(10)(11) human immunodeficiency virus (HIV), (12) acromegaly, (13) and Gaucher's disease. (14) Notably, cross-sectional studies have shown that impact microindentation at the tibia diaphysis discriminates individuals with a history of fragility fracture in some, (15)(16)(17) but not all, studies.…”
Section: Introductionmentioning
confidence: 99%
“…BMSi was measured in all patients by IMI using the handheld microindenter device (OsteoProbe® RUO, Active Life Scientific, CA, USA) at the midshaft of the tibia. Measurements were performed by two experienced operators (NAD and FM) according to our previously published protocol [7,8,18,19]. The patient was placed in a decubitus supine position with the tibia in external rotation.…”
Section: Bone Materials Strength Indexmentioning
confidence: 99%
“…Sosa and Eriksen found that low bone material strength assessed in cortical bone at the anterior tibia constitutes an independent risk factor for all osteoporotic fractures and is related to increased severity of vertebral fractures. Malgo et al compared patients with acromegaly versus controls and found significantly different (worse) bone strength parameters in acromegalic patients as evaluated by microindentation. Acromegaly is a rare disease caused by uncontrolled growth hormone production by a pituitary adenoma.…”
Section: Bone and Cartilage Microindentation Analysismentioning
confidence: 99%